Making health financing work for poor people in Tanzania - Haazen, Dominic, 1954- (World Bank studies, 2012)
Tanzania is currently developing a Health Financing Strategy to provide a medium to long-term road map for a sustainable and integrated health financing system. This book is designed to inform this discussion by providing an analytical basis for the discussion of options, a series of policy options which could be considered in moving forward, and the economic and financial implications of these options. In doing so, it is hoped that this book will help stimulate the discussion of options and help Tanzania develop a health financing strategy which meets its long-term needs. Health financing in T.